Correlation of interfacial stress with the surface roughness of carbon fiber in composites by the improved shear-lag theory. Issue 6 (3rd June 2023) - Zheng, Kaihong; Wang, Yan; Feng, Rongxin; Hameed, M. Saqib; Xu, Jifeng
ABSTRACT: An improved shear-lag model is proposed in this article to study the effects of interface roughness and interfacial stiffness on the mechanical properties of a representative volume element (RVE). The surface roughness of the fiber is represented by grooves distributed around the fiber. The interfacial stiffness is introduced by the cohesive zone modeling (CZM) to study the nonideal adhesion interface. This paper also considered the influence of fiber length on stress transfer. The theoretical model was validated through numerical simulation considering both regularly and irregularly distributed grooves. The results show that the improved shear-lag model can describe the interfacial stress properties accurately. Furthermore, it is found that the influence of surface roughness varies for different interfacial stiffness. The proposed method and results can guide the design and analysis of interfacial modifications in carbon fiber composites. GRAPHICAL ABSTRACT: uf0001